(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
Four wave mixing (FWM) in optical fibers is an undesirable effect to an optical transmission system that can cause a severe limitation in the wavelength division multiplexing (WDM) and reduces the system performance. Within this paper, the normal intensity of RZ robustness modulation and the Modified-Duobinary-Return–Zero modulation (MDRZ) on FWM was investigated. In addition, the performance of the system under the fiber length variation effect was evaluated under the impact of (80) Gbps data rate for both types of modulation format. The results showed that the RZ modulation introduces a minimum (FWM) power of (-54) dBm at (70) kms fiber length, while MDRZ offers FWM power of (-44) dBm at the exactly same fiber length, In-term of the performance of the system at channel 4, a minimum BER was noticed in normal RZ modulation which equals to 2.27´10 - 43 at (-35.31) dBm received power. However, the BER was 4.98´10-15 at the same received power and channel, in the existence of MDRZ modulation format. The finding reveals the progress of RZ modulation in reducing the FWM crosstalk and enhances the WDM system performance even with the impact of high data rates.